Հողամշակ ֆրեզի տեխնոլոգիական պարամետրերի հիմնավորում և տարանջատ տարրերի մեթոդով հողի ու բանող օրգանի փոխազդեցության մոդելավորում - Պետրոսյան, Դանիել; Հովհաննիսյան, Սամվել; Խաժակյան, Դավիթ; Ռաֆայելյաн, Սիմոն (ՀԱԱՀ հիմնադրամ)
Аналитически определены пределы улучшенной величины показателя кинематического режима почвенной фрезы. Для изучения взаимодействия рабочего органа с почвой было проведено дискретное моделирование. Разработан рабочий орган с логарифмическим профилем спирали, который позволяет посредством деформации растяжения отделить срезанную полосу грунта от грунтовой массы и по сравнению с Г-образным ножом обеспечивает снижение сопротивления сдвигу на 30...35 %. Получены формулы для определения радиуса кривизны спирали и величины радиус-вектора. The restrictions in the improved value of the tiller’s kinematic indicator were defined analytically. A soil- tiller interaction model was designed and a more widely used Г-shaped paired blades were tested to obtain comparative results. As a result of the simulation, a new structure of the working body with a logarithmic spiral shape was developed, which enables the separation of the cut soil layer from the soil mass by tensile deformation. The discrete element modeling method was applied to study the interaction between the soil and the working bodies with the proposed logarithmic spiral shape.By modeling the interaction between the soil and the working body, a comparative evaluation of the work efficiency of two different working bodies in sandy, sandy loam and clay soils was made without high material costs. Formulae for determining the radius of curvature of the spiral and the magnitude of the radius-vector have been obtained. Experiments conducted by many researchers have proven that the most effective method of soil compaction is the use of tensile and sliding deformation. It was found out that the magnitude of the force of resistance to the cutting and removal of the soil cutter depends on both the blade and soil types. Blades with a logarithmic spiral shape work particularly well in high- resistant clay soils. As a result, the reduction of the cutting resistance of the soil in tillers working with blades with double cutting plates leads to a corresponding reduction in the specific fuel consumption.
Keywords: Ագրարային ճարտարագիտություն